06.13 A novel preclinical platform for the evaluation of therapeutics for spondyloarthritis (spa) and comorbidities developing in the tga86 murine-tmtnf-driven model. (1st March 2017) - Kranidioti, Ksanthi; Karagianni, Niki; Ntari, Lydia; Argyropoulou, Eleni; Geka, Christina; Denis, Maria C; Kollias, George
Abstract : Background: Spondyloarthritis (SpA) describes a group of diseases characterised by a paradoxical simultaneous bone destruction and formation manifested as axial and peripheral pathologies. TNF is a key pathogenic factor with the strongest evidence of its leading role arising from the therapeutic effect of its inhibition in SpA patients. The TgA86 is a mouse model that overexpresses TNF and exhibits signs of spontaneous SpA. Our objective was to characterise the TgA86 pathology, identify its similarity to human disease and ultimately explore its potential to be used as the basis of a preclinical platform for the evaluation of SpA therapeutics and diagnostics. Materials and methods: TgA86 transgenic mice express deregulated mouse transmembrane TNF and develop with 100% incidence chronic inflammatory arthritis and axial pathology clinically manifested by a characteristic tail bending. We used clinical observations, histopathological analysis, x-ray and μCT radiographic read-outs to establish a standardised pipeline for the evaluation of the TgA86 pathology. Results: Histopathological, x-ray and μCT analysis of the vertebral column revealed the presence of pathological findings closely resembling those observed in human SpA patients. More specifically, disease characteristics included soft tissue swelling, bone erosion, increased bone formation and replacement of the vertebra bar-bell shape with a rectangular shape. Moreover, TgA86 mice exhibited a concomitant development of aortic valve disease, an extraarticular co-morbidity observed in a significant percentage of SpA patients. This data support the similarity of the TgA86 pathology to that of the human disease. We further used a standardised set of the above-mentioned read-outs to validate the response of this model to human therapeutics. TgA86 animals treated with the commercially available human therapeutic Etanercept, exhibited significant amelioration of both peripheral and axial pathologies in a reproducible and dose-dependent manner thus establishing the translational value of this model in the evaluation of human therapeutics. Conclusion: Biomedcode has standardised and validated a novel TgA86-based highly reproducible and sensitive efficacy preclinical platform for the evaluation of therapeutics targeting SpA. This platform can be further used to validate and evaluate the therapeutic effect of the blockade of additional pathological pathways associated with SpA including IL-17, Wnt signalling and others.